2021
DOI: 10.1007/s40831-021-00378-8
|View full text |Cite
|
Sign up to set email alerts
|

REWAS 2022: Developing Tomorrow’s Technical Cycles

Abstract: REWAS, a sustainability driven conference within The Minerals, Metals and Materials Society, has a long history of bringing together academia and industry to exchange and reflect on the latest technology developments available to the metals and materials community. The first edition of REWAS took place in 1999, when the conference was launched as the leading international symposium for recycling technologies, water treatment and clean technologies. 1 At that time, the abbreviation stood for REcycling and WAste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…La pureza del oro en las pepitas, expresada como el contenido de oro en milésimas en relación con otras sustancias presentes, a menudo oscila entre 600 y 950 partes por mil. Esto significa que, en una aleación natural, el oro puede representar una proporción significativa y valiosa (Fleuriault et al, 2021).…”
Section: Presencia Del Oro En La Naturalezaunclassified
See 1 more Smart Citation
“…La pureza del oro en las pepitas, expresada como el contenido de oro en milésimas en relación con otras sustancias presentes, a menudo oscila entre 600 y 950 partes por mil. Esto significa que, en una aleación natural, el oro puede representar una proporción significativa y valiosa (Fleuriault et al, 2021).…”
Section: Presencia Del Oro En La Naturalezaunclassified
“…En segundo lugar, la contaminación por cianuro, destacan las vulnerabilidades en las prácticas actuales de manejo del cianuro en la minería (Fleuriault et al, 2021). Estos eventos subrayan la necesidad crítica de mejorar las estrategias de gestión del cianuro para prevenir futuras catástrofes ambientales, fortaleciendo así la seguridad y sostenibilidad de las operaciones mineras.…”
Section: Razones De La Investigaciónunclassified
“…To date, Aluminum (Al) is by far the most common fuel used in thermites because of its high oxidation enthalpy, availability and low cost. 25 Metal oxides, including MoO 3 , 26 CuO, 27,28 Bi 2 O 3 , 29 Fe 2 O 3 , 30 I 2 O 5 31 have been employed for as long as oxidizers, serving as oxygen sources for the metal oxidation. Recently, experimental studies demonstrated superior initiation characteristics of Al-based thermite using titanium fuel additive [32][33][34] thus bypassing the negative impact of the native alumina (Al 2 O 3 ) coated on aluminum particle limiting mass transport during initiation (i.e., at low temperature, ambient-400 1C).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, they are explored to cut 11,12 , propel 13,14 , disassemble 15,16 , weld 17 , initiate [18][19][20] , release 21 , which actions may be operated under different environments, even in vacuum 22 , underwater 23 and in extreme environments 24 , for both civilian and military applications. To date, Aluminum (Al) is by far the most common fuel used in thermites because of its high oxidation enthalpy, availability and low cost 25 . Metal oxides, including MoO3 26 , CuO 27,28 , Bi2O3 29 , Fe2O3 30 , I2O5 31 have been employed for long as oxidizers, serving as oxygen sources for the metal oxidation.…”
Section: Introductionmentioning
confidence: 99%